Cover page and contents, International Gramsci Journal No.3 2011 - Hawksley, Charles M. (International Gramsci Journal, 2023)
Welcome to the International Gramsci Journal (IGJ) No. 3 of March 2011. IGJ is a new journal that only publishes online. The journal, or individual sections or papers, may be downloaded from our website: http://www.uow.edu.au/arts/research/gramsci-journal/ Each edition of IGJ has two parts. The Gramsci Notes section publishes short pieces of general interest about Gramscian thought, reproduced with permission from other sources. These are selected by the IGJ editor.